THE SELECTION FACTORS OF CONSULTANTS IN SERBIAN AGRO-SECTOR - Mihailović, Branko; Birmančević, Boban; Obradovic, Miloje (Economics of Agriculture, 2014)
The selection of consultants should be paid special attention, because in Serbia, or its agro-sector, the awareness of the criteria for the selection of consultancy services is not sufficiently raised. The research itself is based on the assumption of manager experience and knowledge gained by reading expert books, greeted with skepticism. Thus, the relevance of certain criteria for the consultant selection is in the form of a hypothesis, with the aim to determine the real situation in this fled. Determination of consultant selection basic factors in Serbia is imposed by the law of nature. The process of selecting a consultant starts with defining the requirement of the consultancy task and criteria for the degree of performance of the task. This process usually leads to the reference list that a consultant is supposed to have.